Manajemen Kinerja pada Perusahaan Bisnis dari Manajemen Kinerja Tradisional ke Manajemen Kinerja Baru - Pratista andanitya Siregar; Laura Oktarani Br Torong; Eka Lestari; Zainarti Zainarti (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Traditional performance management has weaknesses and is no longer suitable for business organizations to enter into very tight competition in the global market. Traditional performance management must be abandoned and replaced by implementing a new performance management. Performance management improvements are carried out on an ongoing basis to deliver the best performance of employees, teams and organizations. In order to achieve the effectiveness of performance management, business organizations need to develop supervision in improving performance management. The performance management model which consists of four stages (planning, implementing, reflecting, and compensating) can be used to improve performance management. Keywords: Performance Management